Ecstasy induced acute systolic heart failure and Non-Ischemic Cardiomyopathy in a young female: a rare case report and literature review. Issue 4 (4th July 2019) - Kafle, Paritosh; Shrestha, Binav; Mandal, Amrendra; Sharma, Dikshya; Bhandari, Manjul; Amgai, Birendra; Khalid, Mazin; Sidhu, Jasdeep S; Solaimanzadeh, Isaac; Gayam, Vijay; Surana, Rahul; Dufresne, Alix
ABSTRACT: Ecstasy or 3, 4-methylenedioxymethamphetamine (MDMA) is an illicit recreational drug. Effects include euphoria, increased sensory awareness, and central stimulation. Although various arrhythmias, as well as dilated cardiomyopathy, have been previously noted to occur with chronic use, cardiac toxicities are seldom reported in an acute setting. Herein, we present a 28-year-old female patient with no prior medical condition that presented to the Emergency Department with chest pain following intake of MDMA. Electrocardiographic findings, as well as laboratories, were suggestive of possible Acute Non-ST elevation myocardial infarction. Upon admission, cardiac catheterization revealed patent coronary arteries. Stark regional wall motion abnormalities were observed along with reduced ejection fraction. Acute systolic heart failure was treated with standard medical management. Subsequent reassessment of ventricular function with Echocardiography revealed marked improvement. This article describes a case of MDMA induced heart failure, including details of evaluation, management, and monitoring of patient progress. It brings further attention to potential acute harmful effects of MDMA on cardiac function and viability.